2019
DOI: 10.3390/ijms20122957
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Inhibits the Production of IL-1β-Induced Inflammatory Cytokines and Chemokines in ARPE-19 Cells via the MAPK and NF-κB Signaling Pathways

Abstract: Quercetin, a bioflavonoid derived from vegetables and fruits, exerts anti-inflammatory effects in various diseases. Our previous study revealed that quercetin could suppress the expression of matrix metalloprotease-9 (MMP-9) and intercellular adhesion molecule-1 (ICAM-1) to achieve anti-inflammatory effects in tumor necrosis factor-α (TNF-α)-stimulated human retinal pigment epithelial (ARPE-19) cells. The present study explored whether quercetin can inhibit the interleukin-1β (IL-1β)-induced production of infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(103 citation statements)
references
References 92 publications
7
92
0
4
Order By: Relevance
“…These findings indicated that the JNK1/2 signaling pathway had nothing to do with expression of MCP-1, sICAM-1, sVCAM-1, ICAM-1, and VCAM-1. Some of these observations are identical to the findings reported by Bian et al and Cheng et al, who showed that only ERK1/2 or p38 inhibitors were able to reduce sICAM-1 and MCP-1 levels [30,31]. We believe that this conclusion provides more precise targets for the intervention of monocyte-endothelial adherence.…”
Section: Mediators Of Inflammationsupporting
confidence: 90%
“…These findings indicated that the JNK1/2 signaling pathway had nothing to do with expression of MCP-1, sICAM-1, sVCAM-1, ICAM-1, and VCAM-1. Some of these observations are identical to the findings reported by Bian et al and Cheng et al, who showed that only ERK1/2 or p38 inhibitors were able to reduce sICAM-1 and MCP-1 levels [30,31]. We believe that this conclusion provides more precise targets for the intervention of monocyte-endothelial adherence.…”
Section: Mediators Of Inflammationsupporting
confidence: 90%
“…On the other hand, under the stimulation of inflammatory mediators, such as tumor necrosis factor (TNF)-α, interferon (IFN)-γ and interleukin (IL)-1β, RPE cells produce cytokines and chemokines, including IL-4, -5, -6, -8, -10, -13, -17, IFN-β, IFN-γ, TGF-β, MCP-1 and VEGF. The interaction of pro-inflammatory and anti-inflammatory cytokines ultimately leads to chronic inflammatory responses [39,40]. Inflammatory cytokines can also enhance the secretion of VEGF, which can initiate and cause the pathological CNV and retinal neovascularization of AMD, and macrophages and lymphocytes were found in the active CNV stage [41].…”
Section: Inflammation In Amd Pathogenesismentioning
confidence: 99%
“…Cytokine storm, emerged from prolonged cytokine/chemokine responses during COVID-19, causes ARDS or multiple-organ dysfunction, ultimately leading to physiological deterioration and death [30]. Quercetin, a typical avonoid, is one of the major compounds of FF, LIF, EH, HH, PCB, and LI in LHQW capsule and has been reported to have the effects of anti-in ammation, antiviral, strengthening the endothelial barrier integrity and inhibiting the expression of cytokines [31][32][33][34]. Kaempferol is avonoid found in FF, LIF, EH, FBR, HH, and LI of LHQW capsule, and can protect against in ammation, virus infection, endothelial barrier dysfunction, and cytokines release [35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%